COVID-19 dan Abnormal Return Saham Industri Farmasi - Novita; Ani Wilujeng Suryani (Jurnal Penelitian Teori dan Terapan Akuntansi (PETA), 2022)
The purpose of this study was to determine the effect of the COVID-19 outbreak on abnormal returns and cumulative abnormal returns of pharmaceutical companies' stocks. The research used explanatory research with an event study approach with a 5-day window period is 2 days before the event to 2 days after the event. The sample of this study is the stock of 8 pharmaceutical companies listed on the Indonesia Stock Exchange. Abnormal return data and cumulative abnormal return were analyzed using one sample t-test for normally distributed data and Wilcoxon Signed Rank for data not normally distributed. The results show that the COVID-19 outbreak did not had a significant effect on the pharmaceutical companies's stocks abnormal return, but had a positive and significant effect on the pharmaceutical companies's cumulative abnormal return on the event 2 and event 5. It means that the COVID-19 outbreak contains a good signal for the market, thus increase the stock price.